Risk-return analysis of profit and loss sharing contracts in Islamic banks - El msiyah, Cherif; Madkour, Jaouad; Motahaddib, Aziz (Islamic Banking and Finance Review, 2022)
The purpose of this paper is to make a risk-return analysis of the contracts offered by Islamic banks to demonstrate the economic and financial utilities of profit and loss sharing (PLS) contracts. In this paper, we start from the idea that the increase in the weight of PLS contracts is beneficial for both Islamic banks and the economy as a whole. Our approach is based on a risk-return analysis to identify the financial causes of non-development of PLS contracts and possible ways and trends to stimulate this development. From our analysis, we can conclude that the increase in the weight of sales-based contracts at the expense of PLS contracts is not necessarily the result of good risk and capital management. On the other hand, the low weight of PLS contracts is the result of a lack of risk management and liquidity instruments, a lack of innovation and expertise in risk management and contract design and finally the result of a lack of legal and fiscal frameworks adapted to Islamic banks. This paper proposes a risk-return approach to make the case for increasing the share of PLS contracts, which promotes greater optimization of the risk-return ratio and greater involvement of Islamic banks in the real economy.